Annual report 2018-2019: British Council in Jamaica - Jacobs-Bonnick, Olayinka; Patmore, Jherane; Campbell, Damion; Newsome, Nadene; Young, George; Jacobs, Kiwayne (British Council, 2019)
In this report two programmes indicated to be the focal point of the period were Backstage to the Future and Film Lab. The Backstage to the Future training with a technical skills focus and hands on training for young people from two Live Festivals-Rebel Salute, in Jamaica and in Cuba. Film Lab, the film capacity-building programme was designed to enhance the skill of scriptwriting. Participants were organized into groups and worked together over months to develop the final scripts. The report also discusses the British Council’s support for the development of the Festival Economy, work in education, the Core Skills Training Programme, work in Social Enterprise and Youth Engagement Programmes, commitments and achievements.